Transferred Subspace Learning Based on Non-negative Matrix Factorization for EEG Signal Classification - Dong, Aimei; Li, Zhigang; Zheng, Qiuyu (Frontiers in Neuroscience, 2021)
EEG signals classification has been a research hotspots recently. The combination of EEG signals classification with machine learning technology is very popular. Traditional machine leaning methods for EEG signal classification assume that the EEG signals are drawn from the same distribution. However, the assumption is not always satisfied with the practical applications. In practical applications, the training dataset and the testing dataset are from different but related domains. How to make best use of the training dataset knowledge to improve the testing dataset is critical for these circumstances. In this paper, a novel method combining the non-negative matrix factorization technology and the transfer learning (NMF-TL) is proposed for EEG signal classification. Specifically, the shared subspace is extracted from the testing dataset and training dataset using non-negative matrix factorization firstly and then the shared subspace and the original feature space are combined to obtain the final EEG signal classification results. On one hand, the non-negative matrix factorization can assure to obtain the essential information between the testing and the training dataset, on the other hand the combination of shared subspace and the original feature space can fully use all the signals including the testing and the training dataset. Extensive experiments on Bonn EEG confirmed the effectiveness of the proposed method.